Latvian Sports Regulation in Transition: Navigating Historical Evolution and Contemporary Development Trends - Kameņecka-Usova, Marina; Žīdens, Jānis; Luika, Signe; Donāne, Laine; Agapova, Olena; Stecenko, Ieva; Griķis, Ričards (European Journal of Sustainable Development, 2024)
This comprehensive analysis delves into the intricate realm of sports law and policies in Latvia, exploring the historical evolution, administrative framework, and policy landscapes that shape the country's sports sector. The text highlights Latvia's transition from the Centralized Soviet Model to a more autonomous sports system post-independence, reflecting the nation's historical context and pursuit of sporting excellence. It examines the interaction between EU regulations and internal sports governance, emphasizing the balance between market-regulating rules and legitimate sports governance. The study also discusses recent legislative amendments in response to geopolitical events that has shaken the Eastern Europe, such as the Russian invasion of Ukraine, showcasing Latvia's proactive approach to safeguarding national interests and ethical standards in sports. Furthermore, insights into the implementation of National Anti-Doping Regulations underscore Latvia's commitment to maintaining integrity in sports. The administrative framework involving various stakeholders, including governmental bodies and non-governmental organizations, is analysed to provide a holistic view of sports policy planning and stakeholder engagement in Latvia. Overall, this research sheds light on the evolving landscape of sports law in Latvia and the country's efforts to promote athletic development, fair play, and good governance in sports. The findings will contribute to a deeper understanding of the factors and forces shaping the sports sector in the country. Keywords: sports law and geopolitics, sports governance, sports policies, EU sports law, Latvia